2012
DOI: 10.5380/ce.v17i3.29287
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação De Indicadores Operacionais De Um Serviço De Atendimento Móvel De Urgência

Abstract: RESUMO:O atendimento pré-hospitalar se consolidou no Brasil a partir das normas estabelecidas em portarias ministeriais que culminaram com a implantação de Serviços de Atendimento Móvel de Urgência no país. Neste estudo, realizou-se a avaliação dos resultados produzidos por este Serviço em Teresina-Piauí, analisando a natureza das ocorrências, o tempo resposta e referenciamento dos atendimentos no período de 2005 a 2011. Trata-se de pesquisa avaliativa, descritiva, quantitativa com dados obtidos a partir das f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0
10

Year Published

2015
2015
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 5 publications
1
5
0
10
Order By: Relevance
“…Studies involving the Mobile Emergency Care Service ("SAMU"), regarding the total number of occurrences attended, identified that 10.66% of the occurrences were related to pregnancy, delivery and puerperium, confirming that, during the fertile age, pregnancy and its associated factors motivate a greater search for emergency services. 12 The spontaneous demand stood out; this can be understood as the unexpected arrival of the user to the service, either by acute problems or for reasons that the patient itself considers health needs.…”
Section: Risk Classification At Obstetric Emergencymentioning
confidence: 99%
“…Studies involving the Mobile Emergency Care Service ("SAMU"), regarding the total number of occurrences attended, identified that 10.66% of the occurrences were related to pregnancy, delivery and puerperium, confirming that, during the fertile age, pregnancy and its associated factors motivate a greater search for emergency services. 12 The spontaneous demand stood out; this can be understood as the unexpected arrival of the user to the service, either by acute problems or for reasons that the patient itself considers health needs.…”
Section: Risk Classification At Obstetric Emergencymentioning
confidence: 99%
“…Estes sintomas podem demorar até vinte e quatro horas para aparecer e, por isso, o indivíduo deve ser observado atentamente dentro deste período, de preferência em um hospital. 13,15 O processo de educação permanente impõe uma série de desafios que precisam ser transpostos para tornar-se efetivo. Para garantir a efetividade deste processo e imprimir caráter permanente e continuado, é fundamental inserilo na rotina de trabalho e considerar, portanto, as atividades dentro da carga horária contratual do trabalhador.…”
Section: Introductionunclassified
“…In Brazil the urgency and emergency sectors are identified as incapacitated and problematic areas within the health system, in which the decentralization, regionalization and hierarchy guidelines are insufficiently implemented (1) . In this context, the National Emergency Care Policy and consequently, the Mobile Emergency Care Services, were created in order to manage the health system, from the perspective of Pre-Hospital Care (PHC), organizing the network attention and structuring the national emergency services.…”
Section: Introductionmentioning
confidence: 99%